The effect of Clinical Practice Guidelines on prescribing practice in mental health: A systematic review. (February 2020) - Nguyen, Tony; Seiler, Natalie; Brown, Ellie; O'Donoghue, Brian
Abstract: Clinical Practice Guidelines are succinct evidence-based recommendations and in psychiatry, exist to advise on psychotropic prescribing to effectively treat mental health conditions whilst minimising medication adverse effects. Implementation of psychiatric guidelines have, in the past, demonstrated little and transient impact on clinical practice. How effective prescribing guidelines are in aligning practice with evidence currently is unknown and this systematic review aimed to investigate said efficacy. Literature searches were performed on MEDLINE, EMBASE, and CINAHL up to September 2019 and articles were selected by two reviewers independently with discrepancies resolved by a third reviewer. The review identified 18 eligible articles pertaining to the following conditions: depressive disorders, psychotic disorders, post-traumatic stress disorder, anxiety disorders, bipolar affective disorder, attention deficit/hyperactivity disorder, borderline personality disorder, and opiate addiction with depression guidelines being the most frequently evaluated. Seven studies revealed guidelines effected no change in psychotropic prescribing. The remaining studies illustrated that even when practice was changed, the effect was generally small, emphasising the need to change guideline development and implementation, taking into account obstacles or opportunities specific to psychotropic pharmacotherapy.